Prevalence of burnout and stressors among caretakers of children with cancer at Hospital University Sains Malaysia - Subramaniam, Shamini A/P (2018)
Introduction Cancer has become a leading disease burden among pediatric population globally. Pediatric oncology in this current era is undergoing rapid evolvement in order to achieve optimal care and to reduce mortality and morbidity among patients, in keeping with sustainable development goals (SDG), as aspired by United Nations.1-4On the International Childhood Cancer day in 2018, WHO announced that more than 300,000 children from birth till 19 years old were diagnosed with cancer. The Malaysian Cancer Registry also reported that there were 37 in 100,000 children, have risk of cancer. Advanced treatment modalities and supportive care have increase survival rate and reduce mortality rate, which may contribute to more morbidity, hence higher disease burden among survivors and caretakers.1, 2, 4-12 Majority of children with cancer require frequent and prolonged hospitalization, prolonged school absenteeism, frequent investigations, intensive care or prolonged ventilator support, while some children with poorer prognosis received palliative care. Parental support, understanding and commitment are important to enable compliance and to achieve optimal treatment goals. Caretakers of children with cancer are identified as vulnerable group to suffer burnout, a concept described as emotional exhaustion, reduced performance and depersonalization.13 Stress due to stressors at the expense of lifestyle, psychosocial status, emotional distress and family dynamics modification, poor quality of life, which affectedpatient care.3, 7, 8, 11, 14-17 Validated, Malay version Copenhagen Burnout Inventory (CBI-M), was chosen in this study as it is the newest tool to measure burnout, with good psychometric, freely and easily available in many languages. In addition, the tool can be used to assess exhaustion and fatigue pertaining to personal life, work and service to clients.18, 19The concept of compassion fatigue is closely related or said to be a form of burnout, however it addresses the relational nature of condition, while burnout often related to stressors.20, 21 Stress occurs when there is a mismatch between the ability of a person to cope with the demands of a situation. Stressor is resulted from personal or environmental event that causes stress.22 It has a major influence upon mood, sense of wellbeing, behavior and health.23Studies have shown that cancer related factors, such as disease itself and invasive procedure such as bone marrow aspiration have contributed to parenting stress leading to limitation of their activity and contributing to poor quality of life.8A study also showed differences in culture imposed different responses to stress,as in Chinese group showed lower emotional distress as compared to Caucasions.11, 24Parenting stress needs to be tackled for future intervention.Stressor was measured using General Stressor Questionnaire (GSQ), a good psychometric tool, translated to Malay language. It is a reliable and validated tool to measure the prevalence of stressor.25